Grief counseling among caregivers of terminally ill patients - Fabula, Roselyn Hope B.
With a growing population of individuals diagnosed with cancer in the country every year, family members find themselves taking on caregiving roles without preparation and little support. As the disease progresses to its terminal phase, and the physical decline of the individual becomes more evident, the caregivers experience intense strain while facing multiple losses of health, relationships and a future with the terminally ill family member. The family caregivers may grieve over both the current losses and the anticipation of the ultimate loss through death. Research on grief is usually conducted after death, but this study explored grief pre-loss or the anticipatory grief of nine family caregivers of terminally ill individuals, and how it is experienced within the context of their caregiving. Data analysis on the structured interviews, counseling notes and their results on the Anticipatory Grief Scale revealed that family caregivers experience anticipatory grief characterized by physical, psychological and social manifestations. Their lived experiences provide the background to the experience of anticipatory grief and offer a glimpse into the responsibilities, needs, relationships and cultural factors that affect both their anticipatory grief and caregiving. The study concluded that a targeted intervention for caregivers that includes grief counseling and educational elements is effective for the caregivers of terminally ill patients, as it can positively impact the caregivers and assist them in coming to terms with their anticipatory grief, their present situation and prepare them for the anticipated loss. Furthermore, education on grief and caregivers’ needs should be institutionalized for counselors, health care providers and others who encounter them, so they can offer the support needed by the caregivers and their families.